Konstruowanie linii zbieżnych do danych w rysunku odręcznym - Ułamek, Krzysztof; Pawłowski, Wiesław (Wydawnictwo Politechniki Łódzkiej, 2010)
Tematem pracy jest poszukiwanie konstrukcji linii zbieżnej do danych przechodzącej przez żądany punkt oraz analiza rozwiązań tego zagadnienia pod kątem przydatności w rysunku odręcznym.

The constructions show the problem that the students face: they have to draw a still life object which has many lines that we know are parallel. In the drawing, however, there are not any vanishing points and it is not possible to make use of the horizon which, for compositional reason, is located out of the drawing. Anyway, thanks to observation, we can place at least two from many lines parallel to a given direction into a drawing. This article discusses the various geometric designs solve this problem.
The construction of setting a straight line convergent on two straight lines in free-hand drawing